Atypical Placental Site Nodule (APSN) and Association With Malignant Gestational Trophoblastic Disease; A Clinicopathologic Study of 21 Cases. (March 2015) - Kaur, Baljeet; Short, Dee; Fisher, Rosemary A.; Savage, Philip M.; Seckl, Michael J.; Sebire, Neil J.
<x xml:space="preserve">Abstract</x> The WHO Classification of Gestational Trophoblastic Tumors classifies placental site nodule (PSN) as a benign tumor-like trophoblastic neoplasm. Cases of PSN with atypical features were described [atypical placental site nodule (APSN)] and we started registering APSN in our unit in 2005. The aim of this study is to present our initial experience with these lesions. The Trophoblastic Disease Unit database was searched to identify all patients who were either referred with, or on review were diagnosed with, APSN from September 2005 to May 2013. Case notes and the pathology findings for these patients were retrieved and reviewed. A total of 21 cases of APSN were included, 3 of which were associated with gestational trophoblastic neoplasm on follow-up or review. Malignant gestational trophoblastic disease was associated with 3/21 (14%) cases of APSN, either concurrently or developing/manifesting within 16 mo of APSN diagnosis. None of these patients had raised serum hCG levels either at presentation or follow-up. Presence of APSN should indicate a thorough clinical and radiologic investigation and follow-up if diagnosed on curettage specimens. With increased recognition of this entity and corresponding larger series with longer follow-up, more accurate patient counseling will be possible.